2010
DOI: 10.1371/journal.pntd.0000879
|View full text |Cite
|
Sign up to set email alerts
|

Control of Tungiasis through Intermittent Application of a Plant-Based Repellent: An Intervention Study in a Resource-Poor Community in Brazil

Abstract: BackgroundTungiasis, an ectoparasitosis caused by the female sand flea Tunga penetrans, is an important health problem in many impoverished communities in the tropics. Sand flea disease is associated with a broad spectrum of clinical pathology and severe sequels are frequent. Treatment options are limited.Methodology/Principal FindingsWe assessed the effectiveness of the intermittent application of the plant-based repellent Zanzarin to reduce infestation intensity and tungiasis-associated morbidity in a resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
22
1
1
Order By: Relevance
“…We have previously shown that the regular application of Zanzarin, a repellent based on coconut oil, reduced the attack rate of invading sand fleas by 92%, and almost completely resolved tungiasis-associated morbidity in resource-poor settings in Northeast Brazil [25], [26]. In this study we compared the protective effect of a twice daily application of the repellent with the availability of closed shoes in a rural area in Madagascar, where the crude prevalence of tungiasis varied between 30 to 69% [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the regular application of Zanzarin, a repellent based on coconut oil, reduced the attack rate of invading sand fleas by 92%, and almost completely resolved tungiasis-associated morbidity in resource-poor settings in Northeast Brazil [25], [26]. In this study we compared the protective effect of a twice daily application of the repellent with the availability of closed shoes in a rural area in Madagascar, where the crude prevalence of tungiasis varied between 30 to 69% [6].…”
Section: Introductionmentioning
confidence: 99%
“…The attack rate became zero-or near zero-immediately after the repellent had been applied to the feet regularly. [17][18][19] The major repellent component of Zanzarin is capric acid, a fatty acid from coconut oil. The repellent also contains jojoba oil and Aloe vera, which have an anti-inflammatory effect and presumably also contributed to the rapid reduction of the inflammation of the feet as soon as sand fleas were effectively repelled.…”
Section: Discussionmentioning
confidence: 99%
“…16 We have previously shown that the regular application of a repellent-based coconut oil effectively reduces tungiasisassociated morbidity in lightly and moderately infected individuals. [17][18][19] Here, we test the hypothesis, whether this approach is also effective in extremely severe cases and compare the effectiveness of the regular application of the repellent to the protection provided by closed shoes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] In human tungiasis, more than 97% of all embedded sand fleas are located at the feet. 16 However, at the feet, embedded sand fleas are heterogeneously distributed, with the periungual areas, the heels, and the lateral rim of the foot being predilection sites.…”
Section: 12mentioning
confidence: 99%